Pengaruh Harga, Promosi Dan Kualitas Layanan Terhadap Keputusan Pembelian Di Toko Online Shopee Kota Bengkulu - Royen Stiawan; Arifah Hidayati; Idham Lakoni (Primanomics : Jurnal Ekonomi & Bisnis, 2024)
The aim of this research is to find out how much influence price, promotion and service quality have on purchasing decisions at the Shopee online shop in Bengkulu City. The variables of this research are price, promotion, service quality and purchasing decisions.This research is associative in nature.This research method is quantitative research. Purposive sampling technique. In this research, the data comes from distributing questionnaires (Google Form) which will be distributed online to consumers who have made online purchases. The research population is consumers who have made purchasing decisions on the Shopee application in the city of Bengkulu. Researchers used the hair formula to determine the sample where 16 questions x 10 = 160 respondents. This research uses a Likert scale, with SPSS 22 tools. MethodAnalysisthe data used isvalidity test, reliability, normality test, multicollinearity test, heteroscedasticity test, multiple linear regression analysis, multiple correlation analysis, coefficient of determination test (r²), t test (partial) and f test (simultaneous).The results of this research are; (1) Price influences purchasing decisions at the Shopee online shop in Bengkulu city, (2) Promotion influences purchasing decisions at the Shopee online shop in Bengkulu city, (3) Service quality influences purchasing decisions at the Shopee online shop in Bengkulu city and (4) There is a direct influence Simultaneous Price, Promotion and Service Quality on purchasing decisions at the Shopee online shop in Bengkulu City.